Autosomal recessive spastic paraplegias types 7 and 76 - Galina E. Rudenskaya; Varvara A. Kadnikova; Oksana P. Ryzhkova; Nina A. Dyomina; Inna V. Sharkova; Alexander V. Polyakov (Анналы клинической и экспериментальной неврологии, 2021)
Introduction. Since 2017, the Research Centre for Medical Genetics has been conducting the first clinical and molecular study in Russia of a heterogeneous spastic paraplegia group based on the MPS high throughput sequencing method. Our group of molecularly diagnosed SPGs (types with known genes) includes 122 families with 22 SPG types. This article continues the publication series on the study results.